Musei e digitale - Dragoni, Patrizia (Scripta manent (Ljubljana), 2025)
Communication represents a fundamental function of the museum, especially with regard to the participatory construction of meanings with communities, as emerges from its current definition (Prague, 2022). In light of the diverse and heterogeneous tools and media through which museum communication is expressed, this paper examines, through literature review and selected case studies, some of the digital resources that have recently been implemented or are under consideration for future integration within museums. In fact, although the opening of the institution to the digital can be said to have begun in the 1990s, it was the recent challenge that caused its closure due to the Covid 19 pandemic that acted as a watershed between museums that were already accustomed to the use of technology and those that approached it for the first time in that circumstance. Against the backdrop of this relationship between museum and digital, with a view to strategies valid for the contemporary context and engagement with different audiences, the study outlines the potential benefits of creating and disseminating content through innovative formats.
Keywords: comunicazione museale; musei virtuali; museum communication; museum strategies; muzejska komunikacija; muzejske strategije; strategie museali; technologies; tecnologie; tehnologije; virtual museums; virtualni muzeji